Draft Annual Plan 1983-84 North Eastern Council Shillong - Planning Commission (Planning Commission, 1983)
While the improvement in the rate of utilisation has generated a sense of positive optimism, the Sixth Five Year Plan of the North Eastern Council has reached a crucial juncture in the context of the need to find resources for new commitments and escalation of requirements for vital on-going projects. The Annual Plan exercise for 1982-83 had as its basic stipulation the projection that the year (1982-83) would be the 'hump' year for fund requirements. Expectation was of a gradual tapering off of the fund requirements in the last two years of the Sixth Plan.
North Eastern Council Secretariat